In vitro activities of moxalactam and cefotaxime against aerobic gram-negative bacilli. - Jorgensen, J H (1980)
The in vitro activities of two new beta-lactam antibiotics, moxalactam disodium (LY 127935) and cefotaxime (HR-756), were compared with cefoxitin, cefamandole, cefuroxime, cephalothin, and, in some instances, carbenicillin, gentamicin, and amikacin against aerobic gram-negative bacilli. Test isolates included normally cephalosporin-resistant members of the Enterobacteriaceae and Pseudomonas spp. and a variety of nonfermentative or oxidase-positive bacteria. Both moxalactam and cefotaxime demonstrated impressive in vitro activities against both groups of microorganisms. The two new drugs were clearly more active than any of the other beta-lactam antibiotics against species of Escherichia, Citrobacter, Enterobacter, Klebsiella, Proteus, Providencia, Pseudomonas, and Serratia. An additive or synergistic effect could also be demonstrated with the majority of Pseudomonas and Serratia isolates when either moxalactam or defotaxime was combined with amikacin.